2007
DOI: 10.1111/j.1600-0838.2007.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity on prescription in primary health care: a follow‐up of physical activity level and quality of life

Abstract: To examine whether physical activity on prescription in routine primary care patients would influence physical activity level and quality of life 6 months later. In 2001-2003, 13 Swedish primary health care units took part in an uncontrolled clinical study. If a patient in primary health care needed physical activity preventively or for treatment of a disease and patient-centered motivational counseling found physical activity to be suitable, individualized physical activity could be prescribed. Patients (n=48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 33 publications
10
135
2
6
Order By: Relevance
“…In addition, units do offer events through lectures and courses that can lead to greater awareness and knowledge about the importance of achieving physical activity guidelines for health benefits. As a consequence, it is possible that individuals would feel better prepared and encouraged to engage in additional bouts of physical activity and exercise outside of the referral system and health facilities, thus the role of primary care in increasing physical activity levels would be fulfilled through outreach programs and activities 13,17,36 .…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, units do offer events through lectures and courses that can lead to greater awareness and knowledge about the importance of achieving physical activity guidelines for health benefits. As a consequence, it is possible that individuals would feel better prepared and encouraged to engage in additional bouts of physical activity and exercise outside of the referral system and health facilities, thus the role of primary care in increasing physical activity levels would be fulfilled through outreach programs and activities 13,17,36 .…”
Section: Variablesmentioning
confidence: 99%
“…They occur in accordance with the socioeconomic and cultural differences found in each municipality. Several types of interventions have been utilized including informational lectures, supervised physical activities, and counseling by health professionals 17,18 . International studies have shown a positive relationship between participation in programs to increase physical activity and levels of physical activity, as well as improvements in health conditions of the population 17,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and exercise beyond daily life activities performed over the last 12 months. The answers were combined to calculate the activity index (1 = inactivity, 2 = low activity, 3 = moderate activity, 4 = high activity) (Kallings et al, 2008).…”
Section: Physical Activitymentioning
confidence: 99%
“…Participants also self-reported their level of physical activity (1=inactivity, 4=high activity) (Kallings et al, 2008, Peolsson et al, 2007.…”
Section: Other Measurementsmentioning
confidence: 99%